Chameleon project: a children's end-of-life care quality improvement project. Issue 4 (20th December 2021) - Wolff, Toni; Dorsett, Caroline; Connolly, Alexander; Kelly, Nicola; Turnbull, Jennifer; Deorukhkar, Anjum; Clements, Helena; Griffin, Hayley; Chhaochharia, Anjana; Haynes, Sarah; Webb, Kerry; Manning, Joseph C
Abstract : In response to there being no specialist paediatric palliative care (PPC) team in a region of England, we undertook a 12-month quality improvement project (funded by National Health Service England's Marginal Rate Emergency Threshold and Readmission fund) to improve children's end-of-life care. Improvements were implemented during two plan–do–study–act (PDSA) cycles and included specialist experts, clinical champions, focused education and training, and tools and materials to support identification, care planning and communication. A lead paediatrician with expertise in PPC (10 hours/week) led the project, supported by a PPC nurse (3 days/week) and a network administrator (2 days/week). Children who died an expected death were identified from the child death review teams. Numbers of non-elective hospital admissions, bed days, and costs were identified. Twenty-nine children died an expected death during the 12 months of the project and coincidentally 29 children died an expected death during the previous 12 months. The median number of non-elective admissions in the last 12 months of life was reduced from two per child to one. There was a reduction in specialist hospital (14%) and district general hospital (38%) bed days. The percentage of children who died an expected death who had anticipatory care plans rose from 50% to 72%. The results indicate that a network of clinicians with expertise in PPC working together across a region can improve personalised care planning and reduce admissions and bed days for children in their last year-of-life with reduced bed utilisation costs.